Studying ceramics according to the stratigraphic method: Some examples from the Dvin case-study - Pruno, Elisa (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
This paper explores the methodological framework and preliminary results of the ceramic analysis conducted in Area 1000 of the medieval site of Dvin, during the Armenian-Italian excavation campaigns of 2021–2023. Focusing on the stratigraphic study of pit fills, the research applies a systematic classification and quantification strategy to ceramic assemblages, integrating fabric analysis, typology, and functional assessment. Special attention is given to the concepts of primary, secondary, and de facto refuse, in order to refine interpretations of site formation processes and domestic activity patterns. Through the use of stratigraphic matrices and quantitative ceramic data (sherd count, weight, MNI), the study seeks to reconstruct the dynamics of occupation, abandonment, and urban reorganization following the Mongol conquest. The results underline the importance of integrating ceramic studies into stratigraphic analysis to generate independent chronological frameworks and to better understand the cultural and economic structures of past societies. Future excavation seasons (2025–2026) will aim to further validate this approach, offering new insights into the complex post-urban transformations of Dvin.